2017
DOI: 10.5897/jphe2017.0931
|View full text |Cite
|
Sign up to set email alerts
|

Community based cross-sectional study on knowledge, attitudes and practices towards rabies in Munesa District, Arsi Zone, Southeastern Ethiopia

Abstract: Rabies, one of the oldest and deadliest diseases known to human, is incurable and neglected viral zoonosis which has been threatening the human life for many years despite being entirely preventable. Community awareness play significant role in preventing this fatal disease. Therefore, this cross sectional study was conducted from November to December 2016 with the objective to assess the community knowledge, attitudes, and practices (KAP) regarding rabies in Munesa district, Arsi zone, south eastern Ethiopia.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 16 publications
5
6
0
Order By: Relevance
“…Regarding the causative agent of rabies, the majority of respondents were found to have misperceptions, which were starvation and thirst. This result is consistent with a study in Munesa District, Arsi Zone, Southeastern Ethiopia [20] that reported misperceptions of starvation and thirst as causes of rabies. Similar misperceptions were reported by several scholars from different areas of Ethiopia [21-23].…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the causative agent of rabies, the majority of respondents were found to have misperceptions, which were starvation and thirst. This result is consistent with a study in Munesa District, Arsi Zone, Southeastern Ethiopia [20] that reported misperceptions of starvation and thirst as causes of rabies. Similar misperceptions were reported by several scholars from different areas of Ethiopia [21-23].…”
Section: Discussionsupporting
confidence: 92%
“…Twelve of the studies were published in the previous five years (2018–2023 Gregorian Calendar) ( 28 , 30 , 31 , 34–36 , 38 , 40 , 42 , 47 , 48 , 52 ). Eleven of the studies were conducted in the Amhara region ( 20 , 28 , 31 , 35 , 39 , 41 , 44 , 45 , 47 , 51 , 52 ), 9 in the Oromia region ( 29 , 30 , 33 , 38 , 42 , 46 , 49 , 50 ); 3 in Addis Ababa the capital of Ethiopia’s ( 37 , 43 , 53 ); 2 in the Southern Nations, Nationalities, and Peoples’ Region (SNNPR) ( 34 , 54 ), 1 each in Tigray ( 40 ), and Somalia ( 36 ) regions. The individual study estimates range from 7.50% ( 39 ) to 99.25% ( 51 ) for a good level of knowledge about rabies, 12.55% ( 53 ) to 95.57% ( 49 ) for a favorable level of attitudes, and 4.69% ( 52 ) to 85.68% ( 28 ) for a good level of practices towards rabies prevention ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…From the 27 studies included in the quantitative synthesis, three studies (11.11%) reported factors associated with KAP ( 29–31 ). According to a research report by Abdela et al, being male, living in a peri-urban area, attending formal school, having experienced dog bites, owning a dog, and being trained about rabies were associated with higher KAP scores ( 29 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations